2003
DOI: 10.1248/bpb.26.931
|View full text |Cite
|
Sign up to set email alerts
|

Activation Signal of Nuclear Factor-.KAPPA.B in Response to Endoplasmic Reticulum Stress is Transduced via IRE1 and Tumor Necrosis Factor Receptor-Associated Factor 2

Abstract: Secretory and membrane proteins are correctly folded and glycosylated in the endoplasmic reticulum (ER) by ER-resident molecular chaperones. The ER stores intracellular calcium and is a major signal-transducing organelle releasing calcium in the cytoplasm. Exposure of cells to various pharmacological agents that disturb ER functions, such as calcium depletion from the ER lumen, inhibition of glycosylation or reduction of disulfide bonds, and in physiological conditions, expression of mutant proteins or overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
182
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(193 citation statements)
references
References 36 publications
6
182
1
4
Order By: Relevance
“…Increased IκBα degradation is facilitated by enhanced proteasomal activity, which is highly dependent on the ERAD network. This is distinct from the previously reported mechanisms by which ER stress activates NFκB via the PERK-eIF2α pathway [36][37][38] or by IRE1-mediated activation of TNF receptorassociated factor 2 [39,40]. Interestingly, an increase in ER stress markers and NFκB target genes has been observed in islets of diabetic NOD mice in the prediabetic period [25], raising the possibility that interaction between the pathways is important in the development of type 1 diabetes.…”
Section: Discussioncontrasting
confidence: 78%
“…Increased IκBα degradation is facilitated by enhanced proteasomal activity, which is highly dependent on the ERAD network. This is distinct from the previously reported mechanisms by which ER stress activates NFκB via the PERK-eIF2α pathway [36][37][38] or by IRE1-mediated activation of TNF receptorassociated factor 2 [39,40]. Interestingly, an increase in ER stress markers and NFκB target genes has been observed in islets of diabetic NOD mice in the prediabetic period [25], raising the possibility that interaction between the pathways is important in the development of type 1 diabetes.…”
Section: Discussioncontrasting
confidence: 78%
“…Saturated NEFA are pro-inflammatory in several cell types [43,44] and also cause ER stress [10]. Because palmitate (but not oleate or high glucose) induces ER stress in human islets [10] and there is a crosstalk between ER stress and NF-κB pathways [45][46][47], we explored this mechanism further. We have previously shown that palmitate activates PERK, and also leads to ATF6 and IRE1 activation through depletion of ER Ca 2+ stores [10].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ efflux from the ER activates NF-κB through generation of reactive oxygen species [46] and release of a diffusible, still unknown, NF-κB activator [48]. IRE1 and TNF receptor-associated factor 2 (TRAF-2) can activate NF-κB [45], and stalled protein translation caused by eIF2α phosphorylation decreases IκBα protein availability, consequently activating NF-κB [49]. CPA, a canonical ER stressor, upregulates chemokines and cytokines and activates NF-κB in human islets with an effect comparable with that of palmitate (present data).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress has also been reported to activate NF-B (20). Although it was initially unclear how this might occur, recent studies implicate the IRE1/TRAF2 pathway (21). Some of the gene products induced or activated by the UPR are important in the regulation of inflammatory processes (e.g., XBP-1, CHOP, NF-B, and JNK).…”
mentioning
confidence: 99%